Hot commodities : how anyone can invest profitably in the world's best market - Rogers, Jim, 1942- (New York : Random House, 2004)
"In Hot Commodities, Jim Rogers offers the lowdown on the most lucrative markets for today and tomorrow. In late 1998, gliding under the radar, a bull market in commodities began. Rogers thinks it's going to continue for at least fifteen years - and he's put his money where his mouth is: In 1998, he started his own commodities index fund. It's up 165% since then, with more than
Includes bibliographical references and index.
Keywords: Commodity exchanges; Εμπορεύματα.; Futures market; Διεθνής Αγορά.